2011
DOI: 10.1515/jpem.2011.387
|View full text |Cite
|
Sign up to set email alerts
|

Health promotion intervention in Arab-Israeli kindergarten children

Abstract: Background: Obesity is the most common chronic pediatric disease in westernized societies, with minorities and children from low socioeconomic status being mostly affected. Arab-Israelis are the largest minority population in Israel. Objective: The aim of this study is to examine the prevalence of obesity and to prospectively study the effects of a health promotion, school-based intervention on nutrition and physical activity knowledge and preferences, anthropometric measures, and fi tness in Arab-Israeli kind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 16 publications
(17 reference statements)
1
38
0
Order By: Relevance
“…Nemet et al [30] and Witt et al [35] failed to report their sampling process, which was quite surprising considering the high research rigour their studies otherwise presented.…”
Section: Resultsmentioning
confidence: 99%
“…Nemet et al [30] and Witt et al [35] failed to report their sampling process, which was quite surprising considering the high research rigour their studies otherwise presented.…”
Section: Resultsmentioning
confidence: 99%
“…We recently demonstrated that a school-based combined nutritional and physical activity intervention in Arab-Israeli kindergarten children was associated with an increase in nutritional and physical activity knowledge and preferences, improved fitness and greater decrease in BMI percentiles [10], emphasizing that the school system might be a good platform to reach children in need and implement programs to treat and prevent childhood obesity in minority populations. In the present study, we aimed to determine the longer-term (one year) effects of this program in Arab-Israeli kindergarten children.…”
Section: Discussionmentioning
confidence: 99%
“…However, we were able to reach a relatively high number of participants after one year because many of the participants continued to a neighboring elementary school. Out of the three hundred and forty-two healthy kindergarten children who participated in intervention program [10], we were able to perform the one year follow-up study in 203 kindergarten children (59%; 85 control, 118 intervention). Since usually, the transition from kindergarten to elementary school involves redistribution of the children to several schools, especially in low SES status area were people move often, being able to follow almost 60% of the initial cohort was satisfying.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations